TEACHING SPEAKING WITH READER’S THEATRE - Muhammad Farhan Rafi (E-LINK JOURNAL, 2019)
The study aims to investigate the implementation of  the technique of Reader’s Theatre in the teaching learning process of speaking class at STKIP PGRI Jombang specially at subject of Speaking for Daily Communication. Since The objective of Speaking class is to improve and develop student’s speaking skill fluently, correctly and accurately, the technique of Reader’s Theatre is offered to help students to speak English very well. Students can speak with correct vocabulary, proper pronunciation and good grammar. The subject of the research is students of English department 2017 A and B. The research method isconducted by  describing all activities on speaking for daily communication by using Reader’s Theatre. To collect the data, the researcher uses the instrument by observing the condition of the class during the technique of reader’s theatre applied. The result of the research states that Reader’s Theatre can give a possitive activity to students involved in Speaking class. Students can have a good response toward the Reader’s Theatre technique. Key words: Reader’s theatre, Speaking class